Understanding Individual Materialism: Position of Materialistic Aspirations in the Internal Structure of the Aspiration Index - Julaibib, Julaibib; Hidayat, Rahmat (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Materialistic aspirations, which are individual life goals for happiness based on financial success, fame, and self-image, have seen an increasing trend in our society. This rise in materialistic aspirations negatively impacts individual well-being, the external environment, and social harmony. This study aimed to understand materialistic aspirations in relation to other life aspirations; affiliation, community feeling, conformity, hedonism, physical health, self-acceptance, safety, and spirituality. Data were collected from 413 college students, who were selected using convenience sampling. Data was analyzed using multidimensional scaling. Results showed that hedonism is the aspiration closest to materialistic aspirations and opposite to intrinsic aspirations. Additionally, life aspirations based on the Aspiration Index are categorized into two dimensions and four quadrants. The results of this study provide a perspective on materialism in Indonesia and can have practical benefits, such as creating educational programs on consumer literacy and developing policies related to consumer protection that prioritize some of the Aspiration Index’s domains.